Analisis Prediksi Kebangkrutan Menggunakan Altman Z Score, Springate, dan Interest Coverage Ratio pada Perusahaan Delisting Tahun 2025 - Aprilianti, Refi; Asliana, Endang; Dzulhasni, Sahilly (Jurnal Akuntansi & Keuangan Unja, 2025)
This study aims to predict bankruptcy in companies scheduled for delisting in 2025 using the Altman Z-Score, Springate, and Interest Coverage Ratio (ICR) models, with an initial hypothesis that the Altman Z-Score is the most accurate model. Employing a quantitative method with secondary financial statement data from 5 delisted companies on the Indonesia Stock Exchange (2020-2024), the analysis reveals that the hypothesis of the Altman Z-Score being the most accurate model is rejected due to a high proportion of "grey area" classifications, while the Springate model provides more consistent bankruptcy classifications. Although the ICR indicates the companies' ability to meet interest obligations, overall, all three models suggest an increasing risk of bankruptcy over time, characterized by a decrease in the availability of complete financial statement data and an increase in the percentage of companies categorized as bankrupt. Therefore, strict oversight of financial conditions and enhanced transparency in financial reporting are crucial to prevent bankruptcy risks, especially for companies approaching delisting status.